Prevalence of malaria and associated risk factors among febrile under-five refugee children attending Panyadoli Health Centre III, Kiryandongo District, Mid-western Uganda - Dorcus Acan; Robert Opiro; Benson Musinguzi; Bosco B. Agaba; Simon Peter Alarakol (Malaria Journal)
Abstract Background Malaria presents a big threat to the health of refugees, internally displaced persons, returnees and other such persons affected by humanitarian emergencies, with almost two thirds of these groups of persons living in malaria endemic regions. The aim of this study was to determine the prevalence of malaria and associated risk factors among refugee children < 5 years attending a Health Centre in Panyadoli Refugee Settlement Camp, Kiryandongo District, Uganda. Methods A cross-sectional survey was done between February to April 2022, targeting refugee children < 5 years old seeking healthcare at Panyadoli Health Centre III in Kiryandongo District. Simple random sampling was employed to select 380 participants, who were then tested for the presence of malaria parasites using malaria rapid diagnostic tests and microscopy techniques. Data on risk factors of malaria was collected using a pre-tested and standardized semi-structured questionnaire. Bivariate and multivariate logistic regression analyses was used to identify the risk factors for malaria infections, at 95% confidence interval and p < 0.05. Results Malaria prevalence among the refugee children < 5 years attending Panyadoli HCIII was 12.6% [95% CI: 8.7–18.0]. The associated risk factors for malaria infection included: non-application of indoor residual spraying over the last 12 months [AOR = 4.323; 95% CI 1.231–7.212], history of malaria in children (AOR = 5.861; 95% CI 1.562—8.433], and not sleeping under insecticide-treated nets (AOR = 3.141; 95% CI 0.865—5.221). Conclusion Malaria remains a threat to refugee children < 5 years old at Panyadoli Refugee Settlement Camp. Sustained implementation of IRS should be pursued through expanded geographic coverage and increased application frequency, in conjunction with complementary malaria control measures such as enhanced ITN distribution and IPT for pregnant women, to support long-term malaria reduction.